Media Pembelajaran Animasi 3D Sistem Tata Surya Menggunakan Metode ADDIE - Lyanda, Doli; Halim, R.M. Nasrul; Syakti, Firamon (Prodi Sistem Informasi Universitas Dharma Andalas, 2023)
Learning about the solar system at SMA Negeri 08 OKU for class 11 social sciences is still limited to the use of traditional media such as the use of worksheet books and blackboards as learning media which are less interactive and cannot display astronomical objects in a real way. This research aims to develop and provide 3D animation-based learning media using the ADDIE method as a more interactive and effective learning tool for solar system concepts. 3D animation learning media for the solar system was developed using the ADDIE method. This animation is designed to explain solar system concepts with interesting visualizations, including accurate scale comparisons between planets. This research includes the development of 3D learning animation media, implementation testing in class 11 social studies, as well as evaluation using questionnaires to measure effectiveness and student responses. The research results showed a positive response from students. As many as 70% of students agree that 3D animation of the solar system provides a better understanding of the concept of the solar system,